2011
DOI: 10.1002/dvdy.22528
|View full text |Cite
|
Sign up to set email alerts
|

Translocon‐associated protein subunit Trap‐γ/Ssr3 is required for vascular network formation in the mouse placenta

Abstract: The translocon-associated protein (TRAP, also termed the signal sequence receptor) complex is required for the efficient translocation of secretory and membrane proteins in the endoplasmic reticulum, and is also involved in the endoplasmic reticulum stress-mediated unfolded protein response pathway. To investigate the roles of Trap-g, a TRAP complex subunit, we generated Trap-g knockout mice and found that mutant pups died soon after birth because of retarded embryonic organ growth, especially in the lung. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…For example, we had previously reported that pathogenic variants in the TRAP complex subunit, SSR4 , causes a CDG characterized by developmental and intellectual delays with varying system involvements . Yet, only one mouse model has been generated for studying the developmental role of either the OST or TRAP complex and it involved Ssr3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we had previously reported that pathogenic variants in the TRAP complex subunit, SSR4 , causes a CDG characterized by developmental and intellectual delays with varying system involvements . Yet, only one mouse model has been generated for studying the developmental role of either the OST or TRAP complex and it involved Ssr3 …”
Section: Discussionmentioning
confidence: 99%
“…The individual we report herein, also had severe respiratory distress at birth. When compared to wild‐type litter mates, placenta from Ssr3 KO mice are smaller in total size, but also had widespread vascular network malformations which could explain the IUGR . It is unclear if CDG‐0359 had placenta abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures for whole mount and section in situ hybridization, immunostaining, detection of alkaline phosphatase (AP) activity, and detection of β-galactosidase activity by X-gal staining have been described elsewhere [19], [20]. A cDNA fragment of Dullard (775 bp) spanning the open reading frame was used as the riboprobe.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have been carried out using in vitro reconstituted systems, mainly with microsomal membranes. Its role in membrane protein biogenesis has been emphasised in vivo, where it has been shown that TRAP-α subunit mutant alters mammalian heart development [13], a mutation in TRAP-δ has been related to human congenital disorders of glycosylation [14], and TRAP-γ subunit plays an important role in the process of pronephros differentiation during Xenopus development [15], and appears to be required for vascular network formation in murine placental development [16]. Despite the general importance of the TRAP complex in secreted and membrane protein biogenesis, and the particular involvement of TRAP-γ subunit in development, its membrane topology has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%